Motivation the Investment in Boutique Hotels of the Entrepreneurs in Hua Hin - Cha Am - Pansaen, Nujaree; Samphanwattanachai, Boonyarat (Dusit Thani College Journal, 2020)
The objectives of this research were to study the motivation level of social action, study motivation factors level in Learning Needs Theory, study the nature of business investment needs, and study the tendency of return on investment of boutique hotel-type accommodation business in the area of Hua Hin - Cha-Am District. According to research method, the representative samples were used in this study were total of six entrepreneurs of boutique hotel accommodation business in the area of Hua Hin - Cha-Am District under classification into contemporary style for three entrepreneurs and modern style for three entrepreneurs. Two levels of data collection were collected, including 1) questionnaire by purposive random sampling whereas data was collected using Delphi technique for three times and statistics consisting of Median and Interquartile range were applied for data analysis, and 2) interview whereas content analysis was applied as an interpretation outline of content summary of documents, leading to content analysis from in-depth interview. The finding of the research result indicated that social action of most of the entrepreneurs was maximally motivated in pull factors consisting of their own business progress, more number of tourists, and change in tourist behavior. In maximum motivation level of learning needs, it included planning, orientation, behavior of challenge and will and attempt liking, working venture and high competition and as well as return on investment. In performance measurement, the finding indicated that contemporary style can create maximum added value to the project.